INSTRUCTIONAL PLANNING AS A MEDIATOR OF TEACHER EFFECTIVENESS AND STUDENTS’ LEARNING OPTIMIZATION: A CORRELATIONAL STUDY AT PRIMARY AND SECONDARY SCHOOLS IN NIGERIA - Adewale, Peter Sanjo (International Journal of Education, 2025)
The United Nations' global call for inclusive and equitable quality education has promoted many developing countries including Nigeria to focus on improving the quality of education. This has led to growing recognition of pivotal roles teachers’ quality play in ensuring high-quality teaching and instruction in the classroom. Therefore, this study examines the determinants of teachers’ effectiveness and their effects on students learning optimization in primary and secondary schools in Lagos State, Nigeria. A correlational research design was used for the study. Simple random sampling was used to select 480 respondents. Data were collected using questionnaire titled: Teachers Effectiveness and Students Learning Optimization (TESLO).   Descriptive statistics, T-test, Analysis of Variance (ANOVA) and Pearson Moment Correlation were used to analyse the data collected. Instructional planning/delivery was found to be the foremost factor that determines teachers' effectiveness.  There was a significant difference in the effect of different determinants of teachers’ effectiveness on students' learning optimization (ANOVA at P 0.05). Correlation between teachers' age and teaching effectiveness was determined using Pearson Moment Correlation, the result showed that age has a positive correlation with teachers’ effectiveness (at r = 0.00). Students' learning optimization can be enhanced through instructional planning and teachers’ professional development. Instructional planning should be prioritized in teacher professional development programme. Teachers should individualize instruction, and modify their curriculum, teaching methods, and resources according to students' needs and questions to create a more effective learning environment for their students.